2014
DOI: 10.1007/s00248-014-0534-y
|View full text |Cite
|
Sign up to set email alerts
|

Across-Habitat Comparison of Diazotroph Activity in the Subarctic

Abstract: Nitrogen (N) fixation by N2-fixing bacteria (diazotrophs) is the primary N input to pristine ecosystems like boreal forests and subarctic and arctic tundra. However, the contribution by the various diazotrophs to habitat N2 fixation remains unclear. We present results from in situ assessments of N2 fixation of five diazotroph associations (with a legume, lichen, feather moss, Sphagnum moss and free-living) incorporating the ground cover of the associations in five typical habitats in the subarctic (wet and dry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 46 publications
3
46
0
Order By: Relevance
“…These N 2 fixation rates were also converted to rates of N fixed per unit area with bulk density data from the field (dry weight of the upper 2 cm of each species in a 10 cm 2 plot (N = 4 replicates)). Fixation rates per hectare per year were calculated assuming N 2 fixation activity throughout the growing season (Rousk et al, 2015) during a growing season of around 250 days for peatlands in the Northern Hemisphere with mild winters (Helfter et al, 2015;Zhu et al, 2012) and corrected for an average seasonal temperature of 13 • C, assuming a Q 10 of 3 (Kravchenko and Doroshenko, 2003;Granhall and Selander, 1973;Alexander and Schell, 1973). Total P and potassium (K) concentrations were determined in digestates of dried and ground Sphagnum-microorganism tissue.…”
Section: N 2 Fixation Rates and Elemental Composition Of Sphagnummentioning
confidence: 99%
See 1 more Smart Citation
“…These N 2 fixation rates were also converted to rates of N fixed per unit area with bulk density data from the field (dry weight of the upper 2 cm of each species in a 10 cm 2 plot (N = 4 replicates)). Fixation rates per hectare per year were calculated assuming N 2 fixation activity throughout the growing season (Rousk et al, 2015) during a growing season of around 250 days for peatlands in the Northern Hemisphere with mild winters (Helfter et al, 2015;Zhu et al, 2012) and corrected for an average seasonal temperature of 13 • C, assuming a Q 10 of 3 (Kravchenko and Doroshenko, 2003;Granhall and Selander, 1973;Alexander and Schell, 1973). Total P and potassium (K) concentrations were determined in digestates of dried and ground Sphagnum-microorganism tissue.…”
Section: N 2 Fixation Rates and Elemental Composition Of Sphagnummentioning
confidence: 99%
“…Since the availability of N determines primary production, there appears to be a close link between the N and C cycles (Hungate et al, 2003;Vitousek et al, 2013). This link is especially important in peatlands, which, by storing substantial amounts of C, play an important role in global C cycling (Ruesch and Gibbs, 2008;Clymo and Hayward, 1982). Being ecosystem engineers in peatlands, Sphagnum spp.…”
Section: Introductionmentioning
confidence: 99%
“…However, BNF in mosses is inhibited by N deposition (Gundale et al ., ; Ackermann et al ., ), low moisture content and temperature fluctuations (e.g. Gundale et al ., ; Rousk et al ., , ; Rousk & Michelsen, ). Further, nutritional constraints may also control BNF in boreal and arctic mosses, as free‐living N 2 fixation has been shown to vary with phosphorus (P) and/or molybdenum (Mo) additions in tropical and temperate ecosystems (Silvester, ; Vitousek & Hobbie, ; Barron et al ., ; Wurzburger et al ., ; Jean et al ., ; Reed et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Most knowledge on the compositional and functional aspects of the bryophyte microbiome comes from studies on Sphagnum-dominated peatlands (reviewed by Kostka et al 2016) and the feather moss species mentioned above, as these species cover vast areas in boreal regions. Ground cover of the host-microbial community, however, does not necessarily mirror contributions to fixed nitrogen (Rousk et al 2015). Furthermore, while the cyanobacterial components of bryophyte microbiomes have received the greatest attention, recent studies have shown that methanotrophs may play a greater role in N 2 fixation (Vile et al 2014) and that distinct groups of nitrogen fixers contribute differently to habitat N 2 availability (Rousk et al 2015).…”
Section: Changing Interspecies Interactions In a Warming Climate: Brymentioning
confidence: 99%
“…Ground cover of the host-microbial community, however, does not necessarily mirror contributions to fixed nitrogen (Rousk et al 2015). Furthermore, while the cyanobacterial components of bryophyte microbiomes have received the greatest attention, recent studies have shown that methanotrophs may play a greater role in N 2 fixation (Vile et al 2014) and that distinct groups of nitrogen fixers contribute differently to habitat N 2 availability (Rousk et al 2015).…”
Section: Changing Interspecies Interactions In a Warming Climate: Brymentioning
confidence: 99%